2016
DOI: 10.18203/2394-6040.ijcmph20163388
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the nutritional, education and immunisation profile of children visiting tertiary care centre-is there a gender preference or no?

Abstract: Background: Girls in the country are found to be at a higher risk of malnutrition and growth retardation. Status report of 'Save the Children' highlighted that India is having largest gender survival gap in the World. Aim of the study was to study the nutrition, education and immunization profile of children visiting tertiary care centre, to know gender preference is there or no. Methods: A descriptive study was conducted in, CHRI for a period of 6 months, where parents of all Children aged 5 -15 years were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…In a study done by Neeru Sharma et al [3] more than half (52%) of the mothers want their daughter's educational level to be upto Post graduation and 95% mothers would allow their daughters to select subjects of their own choice and take admission in any college, even out of the state. In another study conducted by Ganavi Ramagopal et al [4] the proportion of male child going to government and private schools was 12.4% and 87.6% respectively and 10.8% and 89.2% respectively in females. They disclosed that there is no difference between boys and girl's education.…”
Section: Attitude Towards Girl Child Education Nutrition and Healthcarementioning
confidence: 85%
See 1 more Smart Citation
“…In a study done by Neeru Sharma et al [3] more than half (52%) of the mothers want their daughter's educational level to be upto Post graduation and 95% mothers would allow their daughters to select subjects of their own choice and take admission in any college, even out of the state. In another study conducted by Ganavi Ramagopal et al [4] the proportion of male child going to government and private schools was 12.4% and 87.6% respectively and 10.8% and 89.2% respectively in females. They disclosed that there is no difference between boys and girl's education.…”
Section: Attitude Towards Girl Child Education Nutrition and Healthcarementioning
confidence: 85%
“…Ganavi Ramagopal and Lala Umadevi [4] has done a study on girl child education, nutrition and health care and in that they found that the proportion of fully immunized females were 63.1% as compared to males were 70.4%. This shows the negligence on the part of health care of girls.…”
Section: Attitude Towards Girl Child Education Nutrition and Healthcarementioning
confidence: 99%